2002
DOI: 10.1177/152660280200900620
|View full text |Cite
|
Sign up to set email alerts
|

Arterial Stenting and Overdilation: Does it Change Wall Mechanics in Small-Caliber Arteries?

Abstract: Endovascular stenting of the rabbit aorta produces a significant decrease in arterial wall compliance and distensibility. Stent overdilation is responsible for a slight additional decrease of compliance downstream from the stent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 39 publications
(51 reference statements)
0
7
0
Order By: Relevance
“…The MVP reproduces the mechanical conditions of lower cyclic strain amplitude within a stent in vivo [46]. The expression of inactive pGSK-3β and Notch1 was examined 7 days following implantation of a BMS.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The MVP reproduces the mechanical conditions of lower cyclic strain amplitude within a stent in vivo [46]. The expression of inactive pGSK-3β and Notch1 was examined 7 days following implantation of a BMS.…”
Section: Resultsmentioning
confidence: 99%
“…The stented MVP fully reproduces the mechanical microenvironment within a stent and mimics the significant decrease in arterial wall compliance and distensibility following stent implantation [46]. A decrease in cyclic strain amplitude within the stent resulted in a marked increase in vSMC cell growth concomitant with an increase in GSK-3β activation and enhanced Notch1 signaling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The trauma of this procedure is often exacerbated by the inability of the balloon to expand the stent fully to its nominal size. This requires a second dilation of the balloon called postdilation, which leads to the overexpansion of the blood vessel wall [6][7][8]. Second, inadequate stent deployment is likely to alter the blood flow conditions increasing the risk of reduced laminary flow and increased pressure gradients.…”
Section: Stents In Percutaneous Transluminal Coronary Angioplastymentioning
confidence: 99%
“…According to the authors, spasm caused by overdilation may be responsible for the decrease in compliance and distensibility measurements distal to the stent. 20 The use of aortic stents has also been found to have a significant effect on the blood supply of the media at the stented segment, which is responsible of an acute decrease in the aortic coefficient of distensibility. 21,22 In vitro models have also shown that endografting of aortic aneurysms results in loss of laminar flow, with propagating vortices along the length of the stented segment.…”
Section: ¤ ¤mentioning
confidence: 99%